Nanoparticles as a toop for drug delivery - A. P. Kaplun; A. E. Stepanov; V. I. Shvets (Тонкие химические технологии)
Common features of nanoparticles as drug delivery venicles and some nanoformulations under development at the chair of biotechnology are considered